MIOSPORAS DEL NAMURIANO y WESTFALIANO DE LA COMARCA MALANZAN-LOMA LARGA, PROVINCIA DE LA RIOJA, ARGENTINA II. DESCRIPCIONES SISTEMATICAS y SIGNIFICADO ESTRATIGRAFICO DE LAS MICROFLORAS (Ameghiniana, 2013)
The second and last part of this paper deals with the description of thirry species among acavate spores with exine adorned by muri, radial fattening or cingulum and cava te anisopolar spores with a cingulum or zone, monolete spores, hilates, alete and monosaccate pollen grains. There are six new species: Secarisporites irregularis, Stenozonotriletes menendezii, Densosporites stellatus, Kraeuselisporites malanzanensis, Kraeuselisporites volkheimerii and Spinozonotriletes hirsutus. On the basis of accumulative diagrams of the species with previous registration, the best represented genera and their possible relation with their parental plants, the conclusion can be reached that the A and B assemblages are of namurian age and that the C assemblage is of westphalian age. A comparison with the fossil megafloras airead y known for the Malanzán Formation shows a difference with data obtained in this study through palynological analysis.